EXPRESSION OF ARTISTIC INTERPRETATION IN NABI JALOLIDDIN’S NOVELS - Matchanova Mastura Baxrom qizi (International Journal of Literature and Language Studies, 2026)
This article examines the problem of artistic interpretation in the novels of contemporary Uzbek writer Nabi Jaloliddin. The study focuses on the representation of human character, interpretation of historical personalities, psychological depiction, and philosophical dimensions of the author’s narrative. The research analyzes the interaction between historical material and artistic imagination, revealing the role of authorial position, literary details, and psychological analysis in creating a meaningful artistic world. The study employs poetic analysis, comparative-typological and structural approaches. The results demonstrate that artistic interpretation in Nabi Jaloliddin’s novels serves as an important means of exploring human nature, historical consciousness, and spiritual values.